Optimization of Single-step Bioconversion Process using Taguchi’s method for the production of Multiple Valuable Fermentation-products - Azmi, Azliin Suhaida; Ngoh, Gek Cheng; Mel, Maizirwan (2010)
The significant of fermentation parameters for multiple valuable fermentation-products from co-culture fermentation of raw unhydrolyzed cassava starch were determined using Taguchi’s methodology in an orthogonal array of L8 using Design Expert v8.0.1. Seven factors were varied at two levels for each factor. The significant factors for the production of multiple valuable fermentation-products, namely ethanol, glycerol and lactic acids, were determined. The result shown that the optimum level for two nutrients which were NPK and urea were at 0.09% (w/w) and 0.8% (w/w), respectively. The optimum concentration of the dry starter of ragi tapai was 10% (w/w) which was best subsequent co-cultured at 3 h later with 10% (w/w) of Saccharomyces cerevisiae. The process was best operated at 30oC of fermentation temperature with 100 rpm of agitation speed.